Remember that patient you saw last week? - Gildfind, S.; Egerton-Warburton, Diana; Craig, S. (Blackwell Publishing, 2014)
Patient outcome feedback has been defined as 'the natural process of finding out what happens to one's patients after their evaluation and treatment (in the ED)'. It seems likely that emergency medicine trainees and Fellows will improve their diagnostic accuracy if they increase the frequency with which they find out what happens to their patients. Not only does this allow testing of their own diagnosis with the final diagnosis, but also allows meaningful feedback on therapies commenced in the ED. We believe that seeking outcome feedback should be more actively encouraged by the ACEM training programme. © 2014 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.